Interview with Yves Lacoste - Zanotelli, Claudio (Geografares, 2020)
This is an interview published in three parts, respectively in the issues 1, 2 and 3 of Geografares from 2000 to 2002. This interview marked the very beginning of this journal. It is the result of the transcription and translation of a radio program dedicated to Yves Lacoste on the famous Radio France Culture in 1994. Then, I conducted a direct interview with Yves Lacoste in 2003 at his home in France. We published, by Editora Annablume, in 2005 the two interviews preceded by the translation of an unpublished text in Portuguese – Da geopolítica às paisagens [From geopolitics to landscapes] – taken from the preamble of a dictionary published by Lacoste: Da geopolítica às paisagens: dicionário de Geografia [From geopolitics to landscapes: Dictionary of Geography], also from 2003.